Directional-dependent pockets drive columnar–columnar coexistence. Issue 29 (24th June 2020) - González García, Álvaro; Tuinier, Remco; de With, Gijsbertus; Cuetos, Alejandro
Abstract : The rational design of materials requires a fundamental understanding of the mechanisms driving their self-assembly. Abstract : The rational design of materials requires a fundamental understanding of the mechanisms driving their self-assembly. This may be particularly challenging in highly dense and shape-asymmetric systems. Here we show how the addition of tiny non-adsorbing spheres (depletants) to a dense system of hard disc-like particles (discotics) leads to coexistence between two distinct, highly dense (liquid)-crystalline columnar phases. This coexistence emerges due to the directional-dependent free-volume pockets for depletants. Theoretical results are confirmed by simulations explicitly accounting for the binary mixture of interest. We define the stability limits of this columnar–columnar coexistence and quantify the directional-dependent depletant partitioning.